Analisis Pencatatan Keuangan dan Pengelolaan Biaya Produksi pada UMKM Rempeyek Bu Ning - Maria Anjelina Baba; Endang Sri Utami (Jurnal Pengabdian Masyarakat Nusantara, 2025)
Micro, small, and medium enterprises (MSMEs) play a strategic role in growing the local economy and creating jobs. However, many MSMEs still face problems in financial recording and managing production costs. Rempeyek Bu Ning MSME experienced this problem because unstructured financial records made it difficult for business owners to monitor cash flow, calculate profits, and determine selling prices in line with production costs. The purpose of this community service activity is to improve the financial management capabilities of MSMEs by helping them record their finances correctly and calculate production costs. Micro, small, and medium enterprises (MSMEs) play a strategic role in growing the local economy and creating jobs. However, many MSMEs still face problems in financial recording and managing production costs. Rempeyek Bu Ning MSME experiences this problem because unstructured financial records make it difficult for business owners to monitor cash flow, calculate profits, and determine selling prices that are in line with production costs. The purpose of this community service activity is to improve the financial management capabilities of MSMEs by helping them record their finances correctly and calculate production costs.